Weather, Demand and Natural Gas Futures Price Volatility in the UK - Yang, Yuntao (2012)
The dissertation deals with modelling of natural gas demand and natural gas futures price volatility with weather variables of the United Kingdom. The first chapter introduces some basic concept like volatility and background information of natural gas market in the UK. The second part is the literature review on related area and topics. The third chapter introduces the terminology and methodology in this dissertation. In the fourth chapter both linear models and non-linear ARIMA models are used to analyse the natural gas demand and the relationship between natural gas demand and heating degree days. In the fifth chapter a GARCH model is used to analyse the natural gas futures price volatility and the relationship with weather surprise. The final part is the conclusion.